Managing Legal Disputes Through Alternative Disputes Resolution - Widjaja, Gunawan (Journal of Ecohumanism, 2024)
Dispute management is an attempt to resolve a dispute or conflict through alternative dispute settlement strategies in a legal context. Alternative dispute resolution methods, such as negotiation, mediation, and arbitration have been widely used in dispute settlement in a variety of situations. The method of research carried out in this research is to discuss the related literature according to the title of the research. The results of this study conclude that alternative dispute settlement strategies can be an effective alternative to litigation in settling disputes. These alternative dispute methods provide advantages such as faster processes, and lower costs, and allow the parties involved to be more active in finding mutually beneficial solutions. In addition, alternative dispute settlement strategies can also help maintain relationships between the parties involved in the dispute. In mediation and negotiation, open communication and cooperation are promoted, which can avoid greater conflict and enable the building of better relations in the future. However, it is important to remember that alternative dispute settlement strategies are not always suitable for every situation. In some cases, litigation can still be the best option, especially when a dispute involves a complex issue or if one of the parties refuses to participate in an alternative settlement effort. Overall, dispute management and alternative dispute settlement strategies are important efforts in minimizing conflict and achieving a fair and beneficial settlement for all parties involved. Understanding the advantages, disadvantages, and appropriate context for using alternative dispute settlement strategies is key in navigating the dispute settlement process well.